Travellers’ Perception towards Airline Industry in India - SANTOSH, B. R.; VARUN KUMAR, S. G. (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019DO - 10.14505//jemt.v10.6(38).09, 2019)
Purpose - The purpose of this study is to examine the factors influencing the perception of air travellers. The study identified three important dimensions namely customer’s expectations, service quality and past experience as an independent variable and customer perception as the dependent variable. Design/methodology/approach – The primary data was collected using a questionnaire to determine the customer’s perception towards airline services. A sample population size of 300 participants who have previously travelled in a flight has been considered for this study. SPSS statistical software has been used for analysing the relationship between the independent variable and the dependent variables. Findings - The study illuminates the differences in perception emphasizing on the various factors that have an influence on their choice. The findings based on the research states that factors such as airport services, reservation and ticketing, inflight services, intangibles and the various dimensions of service quality such as tangibility, reliability, responsiveness, assurance and empathy and customers past experiences have a significant influence on the customer’s perception. Originality of the research – The research paper explains the relationship between customer’s perception and the three important dimensions. In order to improve the perception of customers, the supported hypotheses should be focused on.